The Geography and Concentration of Authorship in the Top Five: Implications for European Economics - Simon Ek; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2018)
We study to what degree authors who publish in the five most prestigious journals in economics have previously published there and in which world region they are based. Although still high, the concentration of U.S.-based and previously published top-five authors has decreased. This trend is driven by increased co-authorship between U.S. and non-U.S. scholars and between scholars with and without previous top-five articles. Only around 5 percent of all articles each year are written solely by first-time authors from outside the U.S., and this share has not increased since the mid-1990s. Against this background, we argue that European institutions should be wary of putting too much emphasis on publishing in these five journals. Both the advancement and diversity of the economics discipline may otherwise suffer.
Keywords: A11; A13; A14; B41; 330; Bibliometrics; Impact of research; Ranking; Research output; Research productivity